(untitled) (CIPEEX, 2024)
THIS ARTICLE ANALYZES THE WORKING CONDITIONS OF WOMEN IN BRAZIL, DESPITE THE CHANGES IN RECENT DECADES. THE RESEARCH AIMS TO UNDERSTAND THE ROLE OF WOMEN IN THE ECONOMY AND SOCIETY, WHICH HAS BEEN SUFFERING TOO MANY CHANGES AND QUALIFICATIONS. OVER TIME, THEY CONQUERED SPACE AND AS A CONSEQUENCE OF THESE ACTIONS THE BREAKDOWN OF SEXIST AND MISOGYNIST SENTIMENT HAS BEEN PART OF THE DESIRED PROGRESS. IN THE PAST, WOMEN FOUND SIGNIFICANT BARRIERS WHEN ENTERING THE LABOR MARKET, OFTEN BEING RESTRICTED TO OCCUPATIONS CONSIDERED "EFFEMINATE" AND RECEIVING WAGES FROM MEN. THE STUDY ANALYZED THE CIRCUMSTANCES OF THEIR WORK, HIGHLIGHTING THE EVOLUTION OF THE INSERTION IN THE LABOR MARKET, DELIMITING PROGRESSIONS AND EVIDENCING THE PRESENT AND ROOTED TREATMENT IN THE BRAZILIAN COMMUNITY, BASED ON CORROBORATING STUDIES. IT IS A NARRATIVE DESCRIPTION BASED ON DATA: GOOGLE SCHOLAR, SCIELO AND REPOSITORIES, WITH A QUALITATIVE, DESCRIPTIVE AND ANALYTICAL APPROACH. FINALLY, SIGNIFICANT DIFFERENCES BETWEEN MEN AND WOMEN WERE IDENTIFIED, RESULTING IN AN EXPLOITATION OF WORKERS, THE PAY GAP, WHICH REACHES AN EQUIVALENT OF MORE THAN 77% COMPARED TO MALES. SUCH EVIDENCE CULMINATES IN THE ALREADY EXPECTED RESULT AND MATERIALIZES THE REALITY LIVED DURING A VERY LONG AND STILL LASTING PERIOD, WHICH SEGREGATES AND DISCRIMINATES FOR MANY TIMES WOMEN. IT IS CONCLUDED THAT THE RESULTS SHOW A BAD HISTORICAL SCENARIO, BEING PRESENT AND PAST. HOWEVER, ALTHOUGH THE REGRESSION IS EVIDENT, A SIGNIFICANT AND UNEXPECTED PROGRESS CAN BE ANALYZED.